ECOLOGICAL AND ECONOMIC ANALYSIS OF PRODUCT LIFE CYCLES - Pryhara, I. O. (Science and Transport Progress, 2008)
In the article the basic stages of life cycle of ecological commodity, the analysis of charges and income on every stage, the ways of prolongation of life cycle of commodity are studied, and also the estimation of life cycle of the commodity is conducted.